(untitled) (Eurasian Scientific Herald, 2022)
In order to prevent counterfeit products from entering the auto parts market, as well as to identify and withdraw products already placed on the market, various ways and methods are used. This article discusses the features and applied methods of combating counterfeit products using the example of Avtooyna LLC, the only automotive glass plant in Central Asia that produces OEM components for the Assembly Line of UzAuto Motors